Expression and functional characterization of odorant‐binding protein genes in the endoparasitic wasp Cotesia vestalis. (24th August 2020) - Zhou, Yue‐Nan; Xie, Shuang; Chen, Jia‐Ni; Wang, Ze‐Hua; Yang, Pei; Zhou, Si‐Cong; Pang, Lan; Li, Fei; Shi, Min; Huang, Jian‐Hua; Chen, Xue‐Xin
Abstract: Odorant‐binding proteins (OBPs) are crucial in insect's olfactory perception, which participate in the initial step of odorant molecules transporting from the external environment to olfactory receptor neurons. To better understand the roles for OBPs in olfactory perception in Cotesia vestalis, a solitary larval endoparasitoid of diamondback moth, Plutella xylostella, we have comprehensively screened the genome of C. vestalis, and obtained 20 CvesOBPs, including 18 classic OBPs and two minus‐C OBPs. Motif‐pattern analysis indicates that the motifs of C. vestalis OBPs are highly conserved in Hymenoptera. The results of tissue expression analysis show that five OBPs (CvesOBP1/11/12/14/16) are highly expressed in male antennae, whereas six other OBP genes (CvesOBP7/8/13/17/18/19) are significantly transcriptionally enriched in female antennae. The results of RNA interference experiments for three most highly expressed OBP genes (CvesOBP17/18/19) in female antennae demonstrate that they are likely involved in parasitic processes of female wasps, as the wasps take a longer time to target the hosts when they are knocked down. Graphical Abstract: We discovered the presence of 20 OBPs in the parasitic wasp, Cotesia vestalis . RNA interference successfully inhibited the mRNA expression of CvesOBP17/18/19, and in vivo behavioral tests showed that the OBP‐deficient wasp lost some of their ability to locate host plants and hosts. In summary, our results demonstrated that CvesOBP17/18/19 are likely involved in parasitic processes of female wasps.